The Role and Function of Integrated Service Posts in Preventing Stunting in The Working Area of The Abeli Health Center - Nurwajid, Yasti; Bahar, Hartati; Karimuna, Sitti Rabbani (Miracle Journal of Public Health, 2023)
Stunting occurs due to lack of nutritional intake, repeated infections, and inadequate psychosocial stimulation, resulting in the risk of morbidity, mortality, and obstacles to children's motor and mental growth. Data on the percentage of short toddlers aged 0-59 months by the Kendari City Health Office, in 2020 it reached 0,80%, Abeli Health Center has the highest percentage of 2.09%, in 2021 it reached 0,22%, in 2022 it reached 0,81%. This study aims to determine the role and function of Integrated Service Posts in preventing stunting in the working area of Primary Health Care Abeli in 2023. This research is a qualitative study with a descriptive approach, and data collection techniques through observation, in-depth interviews, and tracing documents. The research informants were nutrition officers, Primary Health Care Abeli midwives, and Integrated Service Posts cadres. Integrated Service Posts conducts stunting prevention through the 5 table system, focusing on measuring children's body length, providing additional food, motivating Early Breastfeeding Initiation in pregnant women, providing iron and folic acid tablets, and collaborating with BKKBN. Some mothers did not receive Providing Aditional Food, an explanation of the child's height category. In conclusion, the prevention of stunting in Integrated Service Posts is quite good, prevention starts from table 2-5, the table is important in determining nutritional status, especially height status according to age to detect the incidence of stunting, cadres do not explain the category of children's height whether normal or not, causing concern in mothers.